Case Report: Proteomic analysis of cerebrospinal fluid in a retinoblastoma patient - Galardi, Angela; Di Paolo, Virginia; Lavarello, Chiara; Russo, Ida; Romanzo, Antonino; Miele, Evelina; Vito, Rita De; Longo, Daniela; Petretto, Andrea; Locatelli, Franco; Di Giannatale, Angela (Frontiers in Oncology, 2025)
This study focuses on the proteomic analysis of cerebrospinal fluid (CSF) in a patient with stage III retinoblastoma (RB) with the aim to identify molecular changes associated with central nervous system (CNS) relapse. The child received systemic chemotherapy and intrathecal topotecan as CNS prophylaxis, along with enucleation of the left eye. After two chemotherapy cycles, CNS relapse occurred, evidenced by positive CSF findings and magnetic resonance imaging (MRI) showing leptomeningeal involvement at the anterior skull base. The child’s condition deteriorated, and two months later, he died due to progressive CNS disease. The aim of the study was to analyze serial CSF samples collected at different stages of treatment, as well as a control sample, to identify differences in CSF protein expression profiles during CNS RB relapse. Using mass spectrometry, a total of 1,029 proteins were identified across all CSF samples, samples were analyzed in duplicate ensuring technical replication. An unsupervised heatmap revealed 46 differentially expressed proteins. Over-regulated proteins in CSF-RB samples were primarily involved in inflammation, extracellular matrix remodeling, epithelial mesenchymal transition initiation, migration, invasion, and cellular metabolism (PON1, RNPEP, MCAM, NEGR1, NID1, SERPINA1, FAT2, RELN, NEGR1, and SEZ6). These processes are key drivers of cancer progression and metastasis. Proteomic analysis could be valuable in identifying proteins modulated in CSF during disease progression in RB patients, offering potential for new prognostic biomarkers.